Expression of n-MYC, NAMPT and SIRT1 in Basal Cell Carcinomas and their Cells of Origin - Lydia Brandl; Daniela Hartmann; Thomas Kirchner; Antje Menssen (Medical Journals Sweden, 2018)
Deregulated Hedgehog signalling is a driver of basal cell carcinomas. One effector of the Hedgehog pathway is n-MYC. c/n-MYC proteins, NAMPT and DBC1 are linked to SIRT1 in a positive feedback loop that may contribute to tumorigenesis of basal cell carcinoma. In 5 basal cell carcinoma types immunohistochemistry revealed n-MYC, NAMPT and SIRT1 expression. DBC1 was homogenously expressed in all epithelial cells. NAMPT, SIRT1 and c-MYC were expressed in the stratum basale of human and murine skin. In hair follicles NAMPT and SIRT1 were expressed together with c-MYC and n-MYC, except for the matrix, where n-MYC was strongly positive, but c-MYC expression was absent. Therefore, a common pathway connecting n-MYC, NAMPT and SIRT1 may be active in basal cell carcinomas and in their cells of origin. This pathway may contribute to the development of basal cell carcinomas. Targeting factors in the feedback loop may offer novel therapeutic options.